Efektivitas Metode Think Pair Share dalam Meningkatkan Kemampuan Menulis Teks Argumentasi Siswa : The Effectiveness of the Think-Pair-Share Method in Improving the Argumentative Writing Skills - Della Natalia Br Tampubolon; Esra Perangin-angin; Sri Dinanti Br Ginting (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to determine the level of SMP Swasta Hosana Medan students’ ability to write argumentative texts before and after implementing the Think‑Pair‑Share instructional method, and to analyze the extent to which writing ability influences innovation in using Think‑Pair‑Share at SMP Hosana Medan. A quantitative method was used, collecting and analyzing data in numerical form and applying statistical techniques to test hypotheses. The study examines the impact of students’ argumentative writing ability on the innovation of the Think‑Pair‑Share (TPS) teaching method at SMP Hosana Medan. Findings show that this quantitative experimental study was conducted at SMP Hosana Medan during the 2024/2025 academic year, involving 30 students and employing a one-group pretest–posttest design. The research instrument was an argumentative writing test evaluating five aspects of writing: text structure, language use, content accuracy, argument strength, and creativity. In conclusion, implementing Think‑Pair‑Share significantly improved students’ ability to write argumentative texts—in terms of structure, content, and language style—as evidenced by an increase in the number of students achieving “very good” and “good” categories after the learning process.